Developing educational resources for population genetics in R: an open and collaborative approach. (12th July 2016) - Kamvar, Zhian N.; López‐Uribe, Margarita M.; Coughlan, Simone; Grünwald, Niklaus J.; Lapp, Hilmar; Manel, Stéphanie
Abstract: Ther computing and statistical language community has developed a myriad of resources for conducting population genetic analyses. However, resources for learning how to carry out population genetic analyses inr are scattered and often incomplete, which can make acquiring this skill unnecessarily difficult and time consuming. To address this gap, we developed an online community resource with guidance and working demonstrations for conducting population genetic analyses inr . The resource is freely available athttp://popgen.nescent.org and includes material for both novices and advanced users ofr for population genetics. To facilitate continued maintenance and growth of this resource, we developed a toolchain, process and conventions designed to (i) minimize financial and labour costs of upkeep; (ii) to provide a low barrier to contribution; and (iii) to ensure strong quality assurance. The toolchain includes automatic integration testing of every change and rebuilding of the website when new vignettes or edits are accepted. The process and conventions largely follow a common, distributed version control‐based contribution workflow, which is used to provide and manage open peer review by designated website editors. The online resources include detailed documentation of this process, including video tutorials. We invite the community of population geneticists working inr to contribute to this resource, whether for a new use case of their own, or as one of the vignettes from the 'wish list' we maintain, or by improving existing vignettes.